2016
DOI: 10.1101/gr.207456.116
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive variation discovery and recovery of missing sequence in the pig genome using multiple de novo assemblies

Abstract: Uncovering genetic variation through resequencing is limited by the fact that only sequences with similarity to the reference genome are examined. Reference genomes are often incomplete and cannot represent the full range of genetic diversity as a result of geographical divergence and independent demographic events. To more comprehensively characterize genetic variation of pigs (Sus scrofa), we generated de novo assemblies of nine geographically and phenotypically representative pigs from Eurasia. By comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
144
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 49 publications
(61 reference statements)
9
144
1
1
Order By: Relevance
“…It is generally accepted that pigs were domesticated in at least two separate domestication centers, Europe and Asia 26–28 . In our data set of mitochondrial DNA sequences from ancient Chinese pigs, we found both considerable differences in haplotype composition over time and long-term continuity of some haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that pigs were domesticated in at least two separate domestication centers, Europe and Asia 26–28 . In our data set of mitochondrial DNA sequences from ancient Chinese pigs, we found both considerable differences in haplotype composition over time and long-term continuity of some haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The database currently contains 65 data fields for each entry. Our efforts to improve the genome and its annotation are similar to other efforts, for example the sequencing of 12,000 genes to supplement annotation of the pig genome [32, 33,58] and de novo assembly of multiple pig genomes to reveal 1737 protein coding genes that are missing from Ensembl build 10.2 [30]. The online Supplemental data from the latter manuscript was unavailable at the time of the preparation of this manuscript so no comparison could be made.…”
Section: Discussionmentioning
confidence: 99%
“…For genes that were determined to be missing from build 10.2 (Additional file 1) (and for the mis-assembled or duplicated gene artifacts (Additional file 1), we also constructed templates from de novo assemblies derived from Illumina 80 bp reads of the pig alveolar macrophage transcriptome (Dawson, unpublished results) using the de novo assembly algorithm of CLC Genomics Workbench using word size of 20 and a bubble size of 50. When necessary, predicted templates (from bovine or human sequences) were supplemented with porcine expressed sequence tag (EST) assemblies, single ESTs and portions of the published Tibetan (Bioproject # PRJNA291130), Wuzhishan (Bioproject # PRJNA144099), Goettingen (Bioproject # PRJNA291011) [29], Jinhua, Meishan, Bamei, Large White, Berkshire, Hampshire, Pietrain, Landrace, Rongshang and Duroc (Bioproject # PRJNA309108) porcine genomes [30]. ESTs were assembled using CAP3 (http://doua.prabi.fr/software/cap3).…”
Section: Sequence Generationmentioning
confidence: 99%
“…Plenty of archaeological and molecular evidence suggests that pigs were independently domesticated in the Near East and China about 9,000 years ago [1–3]. The effects of geographical divergence, local adaptation and artificial selection result in great phenotypic and genomic diversity among pigs from distinct locations and breeds [4, 5]. In China, there are ∼ 100 native breeds (China National Commission of Animal Genetic Resources 2011), accounting for about one-third of world breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Two main challenges for assembling a state-of-the-art high-quality reference genome are chromosome-scale contiguity and diploid phasing. Previous studies reported multiple de novo assemblies of Chinese native breeds using whole-genome shotgun-based strategies, and shed light on genomic and phenotype diversities of Chinese domestic pigs [4, 810]. Nonetheless, these shotgun-based approaches cannot yield large continuous genome scaffolds, significantly limiting the quality and contiguity of the current Chinese pig genome assemblies.…”
Section: Introductionmentioning
confidence: 99%